Reconstructing runoff components and glacier mass balance with climate change: Niyang river basin, southeastern Tibetan plateau - He, Qiule; Kuang, Xingxing; Ma, Enze; Chen, Jianxin; Feng, Yuqing; Zheng, Chunmiao (Frontiers in Earth Science, 2023)
The southeastern part of the Tibetan Plateau (TP), one of the regions with the largest glacier distribution on the plateau, has been experiencing a significant loss in glacier mass balance (GMB) in recent decades due to climate warming. In this study, we used the Spatial Processes in Hydrology (SPHY) model and satellite data from LANDSAT to reconstruct the runoff components and glacier mass balance in the Niyang River basin (NRB). The measured river discharge data in the basin during 2000–2008 were used for model calibration and validation. Then, the validated model was applied to reconstruct the runoff components and GMB in the Niyang River basin for the period 1969–2013. Results showed that rainfall runoff (67%) was the dominant contributor to total runoff, followed by snowmelt runoff (14%), glacier melt runoff (10%), and baseflow (9%). The NRB experienced a severe loss in GMB, with a mean value of −1.26 m w. e./a (corresponding to a cumulative glacier mass loss of −56.72 m w. e.) during 1969–2013. During periods Ⅰ (1969–1983), Ⅱ (1984–1998), and Ⅲ (1999–2013) glacier mass loss was simulated at rates of −1.27 m w. e./a, −1.18 m w. e./a, and −1.33 m w. e./a, respectively. The annual loss of glacier mass in the northern region of the NRB (−1.43 m w. e./a) was significantly greater than that of the southern region (−0.53 m w. e./a) from 1969 to 2013, largely due to temperature variations, especially in summer months. These findings enhance our understanding of how different hydrological processes respond to climate change and provide a potential method to study runoff components and GMB in other glacierized catchments worldwide.